WDR76 is a RAS binding protein that functions as a tumor suppressor via RAS degradation - Woo-Jeong Jeong (Nature Portfolio, 2019)
Overexpression of RAS proteins is frequently observed in patients with hepatocellular carcinoma. Here, the authors identify an HRAS binding protein, the E3 ubiquitin ligase WDR76, which promotes HRAS degradation, thus functioning as a tumour suppressor in liver cancer